SENSORY EVALUATION OF GREEN TEA FROM LIPPIA MULTIFLORA MOLDENKE LEAVES - Ekissi, Alice Christine; Konan, Amoin Georgette; Yao-Kouame, Albert; Bonfoh, Bassirou; Kati-Coulibaly, Seraphin (European Scientific Journal, ESJ, 2014)
Lippia multiflora Moldenke, a spontaneous shrub from savannah areas, claims many health benefits (against gastrointestinal disorders, anti diarrheal and malaria, fatigue-relieving, diuretic and antioxidant properties). Despite this, its consumption is limited to herbal tea infusion. The objective of the present work is to assess acceptability and organoleptic quality of green tea made from this plant with specific regards to time of storage and geographical origin. To this end, fresh leaves of Lippia multiflora Moldenke were collected from two different geographical areas of CÃ´te dâ€™Ivoire (Centre and North-east). Leaves were processed into green tea according to the orthodox method and stored for one year. Acceptance test and sensory profiling were performed on the teas during storage. No significant differences were found between hedonic scores of teas at different times for the both sampling areas. Also, intensities of sensory attributes of the teas at different storage periods were not significant different. However, acceptability of green tea from Yamoussoukro (Centre) was highly scored than the one from Bondoukou (North-east). Their sensory profiles differ in their aroma characteristics. A lemongrass aroma was perceived in tea from Yamoussoukro while an ocimum grat aroma was found in the one from the north-east. Nevertheless, teas of the two areas, showed similarities for attributes â€œbrownnessâ€, â€œclearnessâ€ and â€œmint aromaâ€. Our study shows that acceptability and sensory characteristics (appearance, taste and aroma) of green tea of Lippia multiflora Moldenke depend on the geographical origin. The processed tea can be stored up to one year without change in the sensory properties.